Klinefelter syndrome diagnosed at autopsy and small-cell lung carcinoma - Haruyasu Sakuranaka; Ryoma Tanaka; Yuji Yamakawa; Shiho Yamada; Komei Igei; Yasuo Asai (Respiratory Medicine Case Reports)
Klinefelter syndrome is characterized by endocrine abnormalities, gynecomastia, female-like body shape, and mild intellectual disability. However, the diagnosis of Klinefelter syndrome is often missed due to the lack of characteristic findings. Computed tomography revealed a mass in the left lung of a 66-year-old man. He was diagnosed with small-cell lung carcinoma. Chemotherapy was administered, but the disease progressed, eventually leading to death. No significant changes were observed in the external genitalia or breast, but the autopsy showed testicular atrophy. XXY cells were seen in fluorescence in situ hybridization, and Klinefelter syndrome was diagnosed. Although chemotherapy causes testicular atrophy, Klinefelter syndrome should be considered in cases of severe testicular atrophy.